2013
DOI: 10.1007/s13311-012-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Chiral Pyrrolyl α-Nitronyl Nitroxide Radical Attenuates β-Amyloid Deposition and Rescues Memory Deficits in a Mouse Model of Alzheimer Disease

Abstract: The generation of reactive oxygen species causes cellular oxidative damage, and has been implicated in the etiology of Alzheimer's disease (AD). L-NNNBP, a new chiral pyrrolyl α-nitronyl nitroxide radical synthesized in our department, shows potential antioxidant effects. The purpose of this study was to investigate the protective effects of L-NNNBP on β-amyloid (Aβ) deposition and memory deficits in an AD model of APP/PS1 mice. In cultured cortical neurons, L-NNNBP acted as an antioxidant by quenching reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Moreover, the ability of NRbt to regulate the activiy of SOD, CAT and the level of GSH was better than that of tempol (P \ 0.05); this occurred because NITs have extensive unpaired spin density distributions (Fig. 1A) compared with tempol [22]. We hypothesized that the protective effect of nitronyl nitroxides against infrasound-induced injury is the result of their ability to scavenge ROS, such as O 2…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the ability of NRbt to regulate the activiy of SOD, CAT and the level of GSH was better than that of tempol (P \ 0.05); this occurred because NITs have extensive unpaired spin density distributions (Fig. 1A) compared with tempol [22]. We hypothesized that the protective effect of nitronyl nitroxides against infrasound-induced injury is the result of their ability to scavenge ROS, such as O 2…”
Section: Discussionmentioning
confidence: 97%
“…We previously synthesized a series of NIT derivatives and found that they were good antioxidants that provided radioprotective effects in vitro and in vivo [20,21]. Recently, we found that the NIT derivative L-NNNBP has good protective effects against bamyloid deposition and memory deficits in an AD rat model of APP/PS1 [22]. Based on our previous research, we synthesized a new cyanuric chloride-based nitronyl nitroxide biradical, 1-chloro-3,5-bis(4,4,5,5-tetramethyl-4-oxylbenzenyl-imidazolidine-1-oxyl-3-oxide)-1,3,5-triazine (NRbt, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Aβ peptides are important in the pathogenesis of AD. Therefore, inhibiting the generation of Aβ and increasing the rate of clearance of this protein, may be potential therapeutic strategies with which to delay the development of AD (4). While the Aβ hypothesis states that the β-amyloid protein is involved in the progression of AD pathology, the etiology remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibited cell apoptosis induced by A␤ exposure. In vivo treatment for 1 month induced a marked decrease in brain A␤ deposition and tau phosphorylation in A␤PP/PS1 transgenic mice [80].…”
Section: Antioxidantsmentioning
confidence: 93%